Risk rationality and risk sharing in financial institutions: An analysis and criticism of Islamic economics - Rohaelis Nuraisiah; Suhendar Suhendar; Moh. Mukri; Azka Nur Diana; Ahmad Dahlan; Mawardi Mawardi (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aimed to establish a philosophical foundation for the conventional financial system from an Islamic perspective, with particular emphasis on usury and risk rationality in the global finance landscape. Using a qualitative library investigative approach, primary data were obtained from articles and books, while secondary data were sourced from financial reports published by various institutions, particularly the Financial Services Authority (OJK). The results showed a positive correlation between the expansion of the interest-based financial sector and rising economic inequality. Conversely, risk-sharing instruments, such as profit-sharing, in Islamic financial institutions presented greater stability in the face of economic shocks and crises. The analysis also identified gaps between philosophical criticism and the practical implementation of contemporary Islamic finance, as well as between the returns on Islamic products and conventional interest rates. In conclusion, ethical and spiritual dimensions should be included in economic theory, as outlined in the Maqâsid al-Sharî’ah. A limitation of this study was the lack of in-depth philosophical analysis grounded in authoritative sources